Peningkatan Fungsi Pengawasan oleh Majelis Pengawasan Notaris Dalam Pencegahan Pelanggaran Kewenangan Dan Tugas Jabatan Notaris - Nanda Ayu Lestari (Faculty of Law Universitas Islam Indonesia, 2022)
This research was conducted to examine the arrangement of notary supervision carried out by the Notary Supervisory Board (MPD) in the Indonesian legal system. In its journey, notary supervision arrangements have increased, both in terms of the authority of MPD and the implementation procedures which are accommodated in Ministry of Law and Human Rights Regulation (Permenkumham) No. 15/2020. The formulation of the problem raised in this study includes the background and urgency of increasing notary supervision by the Notary Supervisory Board? and how are the inspection procedures for the Supervisory Board regulated and used in supervising Notaries? This is a normative legal research which is descriptive analytical with statutory and conceptual approaches. The results of the study concluded that first, the foundation and urgency for the birth of an increase in notary supervision by the Notary Supervisory Board can be seen through Permenkumham No. 15/2020. This regulation is more influenced by sociological factors because of the need to increase the capacity of the MPD in the midst of increasingly complex problems of violations by Notaries. Second, an increase in oversight procedures can be seen by adding an element of reference for inspection by the MPD to clarify the source of the budget for implementing Permenkumham No. 15/2020. In realizing this supervision, of course, it needs to be supported by socialization activities to the fulfillment of adequate facilities and infrastructure.Key Word: Examination, Supervision, Notary Supervisory Board AbstrakPenelitian ini dilakukan untuk mengkaji pengaturan pengawasan notaris yang dilakukan oleh Majelis Pengawas Notaris dalam sistem hukum Indonesia. Dalam perjalanannya, pengaturan pengawasan notaris mengalami peningkatan baik dari sisi kewenangan MPD hingga tata cara pelaksanaannya yang terakomodir dalam Permenkumham No.15/2020. Rumusan masalah yang diangkat dalam penelitian ini mencakup bagaimana latar belakang dan urgensi peningkatan pengawasan Notaris oleh Majelis Pengawas Notaris? dan bagaimana tata cara pemeriksaan Majelis Pengawas diatur dan digunakan dalam mengawasi Notaris? Penelitian ini merupakan penelitian hukum normatif yang bersifat deskriptif analitis dengan pendekatan perundang-undangan dan pendekatan konseptual. Hasil penelitian menyimpulkan, pertama, landasan dan urgensi lahirnya peningkatan pengawasan Notaris oleh Majelis Pengawas Notaris dapat dilihat melalui Permenkumham No.15/2020. Dalam peraturan tersebut lebih banyak dipengaruhi oleh faktor sosiologis karena kebutuhan peningkatan kapasitas MPD di tengah persoalan pelanggaran oleh Notaris yang semakin kompleks. Kedua, peningkatan tata cara pengawasan terlihat dengan menambah unsur acuan pemeriksaan oleh MPD hingga mempertegas sumber anggaran pelaksanaan Permenkumham No.15/2020. Dalam merealisasikan pengawasan ini tentu perlu didukung dengan kegiatan sosialisasi hingga pemenuhan sarana dan prasarana yang memadai.Kata-kata Kunci: Pemeriksaan, Pengawasan, Majelis Pengawas Notaris